Study the effect of using the electrical stimulation upon long jump efficiency - Kasem, Sameh; Dreibat, Bashar; Mahmood, Lobna (Latakia University Journal -Medical Sciences Series, 2018)
The current study aimed to develop the maximum muscle strength of the long jump players by using electrical muscular neural stimulation and knowing wether if this applied laboratory experiment had an effort on the completion in long jump. The research sample consisted of 18 students from the first secondary students. The experimentشم شححقخشؤا ts . the experiment muscle strenghtose a programmeermong jump players by using electrical muscular neural approach has been used in two equivalent groups (experimental – controlled).The controlled group underwent of two training units in long jump weekly for five weeks. The experimental group in addition to that, they had three electrical stimulation sessions weekly for five weeks. The achievement in long jump has been measured before and after the experiment for the two groups . The study found that there is a positive effect of the electrical stimulation on the muscle strength and there is a noticeable improvement of electrical stimulation on the completion in long jump, but is not statistically significant. Thus, we recommended the need to develop training programs that contain the use of electrical stimulation as a method to develop muscle strength . دراسة أثر استخدام التحفيز الكهربائي على فعالية الوثب الطويل هدفت الدراسة الحالية إلى تنمية القوة العضلية القصوى لدى لاعبات الوثب الطويل من خلال استخدام التحفيز الكهربائي العضلي العصبي ومعرفة فيما إذا كان للتجربة المطبقة مخبرياً أثر على الإنجاز في الوثب الطويل . تكونت عينة البحث من 18 طالبة من طالبات الأول الثانوي وتم استخدام المنهج التجريبي بأسلوب المجموعتين المتكافئتين (تجريبية – ضابطة). خضعت المجموعة الضابطة لوحدتين تدريبيتين بالوثب الطويل أسبوعيا لمدة خمسة أسابيع كما خضعت المجموعة التجريبية بالإضافة لذلك إلى ثلاث جلسات تحفيز كهربائي أسبوعيا ولمدة خمسة أسابيع .وقد تم قياس الإنجاز بالوثب الطويل قبل تطبيق التجربة وبعدها لكلا المجموعتين وكذلك تم قياس القوة العضلية القصوى لكلا المجموعتين قبل تطبيق التجربة وبعدها بواسطة جهاز مصمم لهذا الغرض وتمت المقارنة بين المجموعتين. توصلت الدراسة إلى أن هناك تأثيراً إيجابياً للتحفيز الكهربائي على القوة العضلية مع وجود تحسن ملحوظ في مسافة الوثب الطويل مع أنه غير دال إحصائياً ومن هنا أوصينا بضرورة الاهتمام بوضع برامج تدريبية تحتوي استخدام التحفيز الكهربائي كوسيلة مخبرية لتنمية القوة العضلية.